Will you stay? a novel - Norhafsah Hamid (Iman Publication Sdn Bhd, 2023)
"If you love Allah and take care of your relationship with Him, He will take care of the people whom you love. Amy is a 30-year-old doctor who strives to live a meaningful life, choosing to focus on enjoying the company of her friends and committed in nurturing her faith. The unexpected presence of someone from her friend's past stirs up feelings within her. What she was afraid to dream of before this, presented itself to her like a ray of hope from God. Just as her newfound happiness begin to colour her life, her faith is put to the test. Will love stay or will it leave? Will she surrender herself to the One whose love is eternal? In this book, award-winning author Norhafsah Hamid takes reader on a heart-warming journey of understanding what it means to love compassionately and with mercy. For that is the kind of love that will lead us back to God.